GOOD GOVERNANCE, KEBIJAKAN PUBLIK, DAN DEMOKRASI LOKAL: STUDI PADA PEMERINTAH KABUPATEN LAMONGAN - Moh Sa’diyin; Sutopo Sutopo (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The implementation of good governance principles plays a crucial role in improving the quality of public policy and strengthening local democracy in the era of regional autonomy. Lamongan Regency, as one of the developing regions in East Java Province, has demonstrated various efforts to establish good governance through enhanced transparency, accountability, public participation, and innovation in public services. This study aims to analyze the implementation of good governance in the formulation and implementation of public policies and its implications for strengthening local democracy in Lamongan Regency. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through document analysis, observation, and examination of government policy documents and performance reports. The analysis was conducted using the perspectives of good governance, public policy, and local democracy. The findings indicate that the Lamongan Regency Government has implemented good governance principles through improved public service systems, information transparency, and community involvement in regional development planning. However, public participation in the policy-making process remains largely procedural and has not yet reached a substantive level. In addition, the influence of local political elites in policy formulation continues to pose challenges to broader public representation. The study concludes that the implementation of good governance has positively contributed to improving public policy quality and strengthening local democracy in Lamongan Regency. Nevertheless, greater efforts are needed to strengthen public participation mechanisms, enhance community capacity, and optimize transparency and accountability to foster a more inclusive, participatory, and sustainable local democracy.